International collaborative validation of intraneural invasion as a prognostic marker in adenoid cystic carcinoma of the head and neck. Issue 7 (24th July 2014) - Amit, Moran; Binenbaum, Yoav; Trejo–Leider, Leonor; Sharma, Kanika; Ramer, Naomi; Ramer, Ilana; Agbetoba, Abib; Miles, Brett; Yang, Xinjie; Lei, Delin; Bjørndal, Kristine; Godballe, Christian; et al.
Abstract Background The purpose of this study was to characterize the incidence, pattern of spread, and prognostic correlation of nerve invasion in patients with adenoid cystic carcinoma (ACC). Methods Using 3 different pathological categories of perineural invasion, intraneural invasion, and perineural inflammation, we investigated the prognostic value of nerve invasion in a total of 495 ACCs from 9 international patient cohorts with median follow‐up 90 months (range, 12–288 months). Results Of 239 patients (48%) with nerve invasion, 174 (73%) had perineural invasion, 65 (27%) intraneural invasion, and 37 (15%) perineural inflammation. Multivariate Cox regression analysis identified tumor site (p = .008; hazard ratio [HR] = 1.8; 95% confidence interval [CI] = 0.07–3.7) and intraneural invasion (p < .001; HR = 5.9; 95% CI = 0.8–12.3) as independent prognostic markers for both overall survival (OS) and disease‐specific survival (DSS), but not of distant metastases. Conclusion Although perineural invasion has no impact on survival, intraneural invasion is an independent predictor of poor prognosis. Recognition of intraneural invasion may help optimize treatment of patients with head and neck ACC. © 2014 Wiley Periodicals, Inc. Head Neck 37: 1038–1045, 2015